Subsurface utility engineering for municipalities : prequalification criteria and scope of work guide - Anspach, James H.; Scott, C. Paul (American Society of Civil Engineers, 2019)
Subsurface Utility Engineering for Municipalities: Prequalification Criteria and Scope of Work Guide is a resource for understanding subsurface utility engineering (SUE) and bringing up-to-date practices to the application of SUE for public works projects. SUE incorporates existing and emerging technology to identify, characterize, and map underground utility facilities throughout the project development process. This book answers basic questions about SUE, such as, "What is it?", "How is it used?", and "What is its future?" Also includedare chapters on consultant prequalification criteria and a checklist of scoping items that affect costs and scheduling. This report will be a valuable resource for engineers, contractors, and project owners working to improve the quality and efficiency of public work projects
Sponsored by the Utility Risk Management Division of the Utility Engineering and Surveying Institute of ASCE.
Keywords: Underground utility lines.; Public utilities.; Project management.; elektronické knihy; electronic books